Application of DR4 and BM100 Biodegradability tests to treated and untreated organic wastes - Godley, Andrew R.; Lewin, Kathy; Frederickson, Jim; Smith, Richard; Blakey, N. (Cranfield University, 2007)
The aerobic DR4 and anaerobic BM100 biodegradability tests are currently applied in England and Wales for monitoring the reduction in biological municipal waste (BMW) achieved by mechanical biological treatment (MBT) plants (Environment Agency 2005). The protocol is applied only when outputs are landfilled and is based on estimating the reduction in potential biogas production between the MBT input, municipal solid waste (MSW), and all of the landfilled outputs, using the BM100 test. As this is a long term 100 day test the more rapid 4 day DR4 test may also be applied as this has been shown to correlate with the BM100 test. We have now applied the DR4 and BM100 tests to 132 organic waste samples including untreated and treated BMW and specific organic wastes. The results indicate that the correlation between the DR4 and BM100 tests has proved valid for mixed MSW derived BMW wastes. However when both tests are applied to specific organic wastes such as turkey feathers, cardboard packaging waste and pizza food wastes the correlation between the tests is less strong. It is concluded that the use of the DR4 and BM100 test correlation is valid for its designed application (monitoring MBT processes treating MSW derived mixed BMW), but that caution should be exercised when applying both tests to specific single component organic wastes.